LINGUA ACADEMICA: LINGUISTIC SOCIAL JUSTICE FOR INTERNATIONAL MOBILITY AT HIGHER EDUCATION - Kwelju, Siusana (Universitas Negeri Malang, 2022)
The surge in the use of English has escalated in the higher education sector due to the drive of advancing university ranking world-wide. Major universities from expanding circle countries, including Indonesia, are motivated to send their academic staff and students for short-term mobility programs organized by top world-class universities which are normally situated in inner-circle countries, as faculty and student mobility is essential for developing international quality education. Standardized English proficiency tests are the tools for selecting candidates, as native speaker’s English is still regarded as the norm for lingua academica. Therefore, those who receive the access for mobility are always the same people who have already received some academic experiences overseas. With this in mind, we need to challenge the ideology of native speakerism and start embracing the concept of multilinguality. Yet, this is not an easy task to change the deep-rooted ideology. Forty-nine out of 57 college students (82%) of a reputable English Department in Indonesia, for example, still believed in native speaker standards, although they were aware that they could not attain them. In fact, based on socio-psychological and neurobiological evidence, multilinguality unnecessarily impairs intelligibility.